Cardioprotective effects of the electrolyte solution sterofundin and the possible underlying mechanisms - Chen, Min; Xiao, Yingying; Zheng, Jijian; Zhao, Peibin; Cheng, Lin; Jiang, Chuan; Zheng, Sixie; Wang, Zheng; Sun, Sijuan; Ye, Lincai; Chen, Guozhen; Zhang, Hao; et al. (Frontiers in Pharmacology, 2025)
BackgroundSterofundin (SF) is one of the most widely used electrolyte solutions in almost all areas of medicine, with particular importance in intensive care. It provides powerful correction of acid-base imbalances, ion fluctuations, and impaired energy metabolism, which are the three most important characteristics after myocardial infarction (MI). However, whether and how SF protects the heart from post-MI damage are largely unknown.Methods and ResultsPretreating mice with SF before MI surgery reduced the number of reactive oxygen species (ROS)-positive and TUNEL-positive cells. As a result, the infarcted area cardiac fibrosis in the MI mice was reduced and cardiac performance in the MI mice improved. Moreover, RNA-seq analysis demonstrated that SF caused the gene expression profile of MI mice to shift toward that of sham mice, with a significant decrease in apoptosis-, ROS-, and inflammation-associated gene enrichment. RNA-seq analysis also demonstrated that SF induced the upregulation of autophagy-associated gene enrichment. Western blotting confirmed the RNA-seq analysis results, showing that SF induced the upregulation of an autophagic flux. When the autophagic flux was blocked with the autophagy inhibitor 3-methyladenine, the protective effect of SF was reduced.ConclusionSF protects the heart from post-MI damage, and one of the underlying mechanisms could be its autophagy modifications. This study is the first to reveal a previously unrecognized role of electrolyte solutions in post-MI intensive care.